Not Invented Here: Institutional resistance to practical solutions - Zion Lights; Kristian Niemietz; Christopher Snowdon (Institute of Economic Affairs (IEA), 2025)
[Foreword:] The theoretical advantage of single-issue pressure groups is that they can form broad coalitions, gathering people from across the political spectrum who need not agree on anything other than the group's single issue. For example, Women Against State Pension Inequality (WASPI) is a group that campaigns for financial compensation for women affected by the increase in the state pension age. That is all they do. WASPI do not express a view on whether or not Britain should rejoin the EU, abolish the monarchy, convert the House of Lords into an elected upper chamber, or replace the First Past The Post electoral system with Proportional Representation. With that strategy, they have managed to attract support from many different corners of the political spectrum without attaching themselves to any of those. Curiously, though, many high-profile single-issue pressure groups are not like that at all. Black Lives Matter (BLM), Extinction Rebellion (XR), Just Stop Oil (JSO), Mermaids, the Stop the War Coalition (StWC) and the Palestine Solidarity Campaign (PSC) are very much not cross-ideological broadchurch coalitions. They are remarkably politically homogenous, including on issues that have nothing to do with their stated cause. They draw almost all of their support from one specific corner of the political spectrum. This is because groups that present themselves as single-issue campaigns often pursue unstated companion causes, the most common one of which is anti-capitalism. The most clear-cut example of this is BLM UK, where the companion cause is not 'unstated' at all, but prominently stated on their FAQ page ('We are […] all anti-capitalists'1 ) and on their GoFundMe page ('Black Lives Matter UK (BLMUK) is […] guided by a commitment to dismantle […] capitalism'2 ). Similarly, XR also regularly tweet about their anti-capitalist orientation. Why would a pressure group do that? Why would they deliberately limit their appeal to one corner of the political spectrum, thus foregoing the main advantage of being a single-issue group? And why would a movement distract from its primary cause by adding an unrelated secondary one? The answer is that for such movements, the primary and the secondary causes are not unrelated at all. For an anti-capitalist, every social problem is really just downstream from capitalism. From that perspective, an 'ally' who is not committed to dismantling capitalism is not a useful ally at all, and there is no harm in losing them. The useful allies are those who would not bother joining the group if it did not have a distinct anticapitalist vibe. (...)
Keywords: 330